Análise do desempenho e da dinâmica de robôs omnidireccionais de três e quatro rodas - Hélder Filipe Pinto de Oliveira (2008)
Omni-directional robots are increasingly popular due to its improved mobility when compared with more traditional robots. Their usage is more prominent in many robotic competitions where performance is critical.To achieve a high level of performance it is very important the availability of a good dynamical model for the robot. That motivates this work where are sought models and the procedures to estimate its parameters. Once the models are validated through real data they can be used to compare the performance of different configurations.Each robot's performance can be evaluated in terms of maximum speed, acceleration and power consumption. Typical omni-directional configurations use three or four wheels. The relative advantages of each configuration are therefore evaluated using a reconfigurable robot.For robots with the same kind of motors was found that a four wheel configuration presents more friction, higher maximum speed, power consumption and complexity when compared with the three wheel case.